The Economics of Assisted Reproduction - Sherrie A. Kossoudji (Institute for the Study of Labor (IZA), 2005)
Typically, when two people decide to become parents, they procreate by copulation and produce a child. What do people do if, for some reason, they can?t produce their own children but want to be parents? Today, a prospective parent can go to the web, drop a vial of sperm from a donor with specific selected characteristics into a ?shopping cart? and have that sperm delivered in twenty-four hours. Similarly, one can sift through the profiles and pictures of women who are egg donors and select eggs from women with desired characteristics and arrange an egg delivery. These markets are two segments that loosely fall under the rubric of Assisted Reproduction Technologies (ART), which is a shorthand term for the numerous procedures aided by technology used to produce a baby. This primer in the economics of assisted reproduction introduces some of the economic dilemmas brought about by new reproductive technologies. Now the cost of producing children can radically differ among people of similar incomes and values because a prospective parent may have to pay to gain rights to the genetic components that build the child.
Keywords: J16; J13; 330; fertility; women's labor; gender; Fruchtbarkeit; Markt; Familienökonomik; Ethik; Theorie; Welt; Reproduktionsmedizin